Career courage : discover your passion, step out of your comfort zone, and create the success you want - Kelley, Katie C. (American Management Association, 2016)
Career Courage serves as a personal coach through the soul-searching and planning process ahead, whether you're a college grad contemplating choices, a seasoned professional seeking new directions, or a stay-at-home mom preparing to reenter the workplace. Packed with exercises and stories of inspiring second acts, the book poses tough questions about motivation, confidence, character, risk tolerance, and more.